Educating to transform: Violence, not here! (Research, Society and Development, 2022)
Since 2012, the scientific community has recognized the connection between child abuse, domestic violence and animal cruelty, indicating that probably where there is animal cruelty there can be child abuse/domestic violence and vice versa. The objective of this project is to spread information about the Link Theory, to make the community aware of responsible custody, inform the academic community on the subject and demonstrate the importance of the veterinarian in this process. After a period of two months of recruitment and creation of a discussion group, virtual meetings were held to discuss the project, and mainly, to draw up a schedule composed of the activities that would be carried out. 23 postagens were published on topics related to the connection between animal abuse and domestic violence. The project's page on the social network Instagram produced 23 postagens, obtaining a total of 208 followers. The information provided on the page reached mostly women of different age groups, with 38% between 18 and 24 years old and 32.7% between 25 and 34 years old, and from various locations. The use of social networks is essential nowadays as it is a tool that allows the mobilization and participation of the population, and can impact directly or indirectly. In this way, several people were oriented on the relationship between mistreatment of animals and domestic violence through the project, multiplying this theme for the population.